2020
DOI: 10.1371/journal.pone.0231303
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and TB in migrant miners communities of origin in Gaza Province, Mozambique: The need for increasing awareness and knowledge

Abstract: Background As part of ongoing efforts to generate evidence needed on HIV and tuberculosis (TB) to inform policies and programs aimed to improve the health outcomes of migrants and communities affected by migration and mining, a preliminary investigation was conducted through a biological and behavioral (BBS) approach related to HIV and TB in two communities of origin of migrant mineworkers in Gaza Province. The main objective was to determine the prevalence of HIV and the rates of asymptomatic infection by TB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
(29 reference statements)
1
15
1
Order By: Relevance
“…Finally, INS implementation role has expanded over the years from governmental collaborator to primary implementor. Experience with the BBS surveys positioned INS as the key institution to lead the Mozambican arm of a multi-country study funded by the International Organization for Migration (IOM) focusing on miners and their communities [21]. Subsequent studies that have benefited from the human resources, institutional structures and experience gained through the implementation of BBS include the TB Prevalence Survey, Violence Against Children Survey (VACS), Service Availability and Readiness Assessment (SARA), and the upcoming Population-Based HIV Impact Assessment (PHIA) survey.…”
Section: Workforce Development and Institutional Capacity Buildingmentioning
confidence: 99%
“…Finally, INS implementation role has expanded over the years from governmental collaborator to primary implementor. Experience with the BBS surveys positioned INS as the key institution to lead the Mozambican arm of a multi-country study funded by the International Organization for Migration (IOM) focusing on miners and their communities [21]. Subsequent studies that have benefited from the human resources, institutional structures and experience gained through the implementation of BBS include the TB Prevalence Survey, Violence Against Children Survey (VACS), Service Availability and Readiness Assessment (SARA), and the upcoming Population-Based HIV Impact Assessment (PHIA) survey.…”
Section: Workforce Development and Institutional Capacity Buildingmentioning
confidence: 99%
“…Research has noted that the migrant nature of work is characterised by access to commercial sex work, high alcohol use and low condom use. 20,21 The sociocultural and structural conditions that are fostered by these illegal mining communities appear to exacerbate sexual health inequalities and sexually transmitted infections among the people who live and work in these mining communities. There is need for STIs prevention and testing service delivery models that incorporate STIs and HIV testing and treatment outreach in hard to reach areas including illegal gold mining outposts.…”
Section: Discussionmentioning
confidence: 99%
“…In this survey conducted on residents of two migrant mineworkers communities of origin in Gaza Province, Mozambique, it was found that overall knowledge of HIV was low, in which only one in four persons living in these mining communities had comprehensive knowledge about HIV, whereby is within average according to a study that took place in three African countries and estimated comprehensive knowledge of HIV is below 50% in all the three study sites [ 10 ]. The participants from P. Lumumba had higher level of knowledge about HIV likely because this community is located in an urban environment that offers greater exposure to both social media and social interventions to reduce the impact of HIV infection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural changes and the adoption of safer sexual habits, such as consistent condom use and reduction in the number of sexual partners, play a significant role in decreasing HIV transmission. Influenced by personal awareness on how HIV transmission can be prevented, especially targeting vulnerable populations, educational programs designed to increase comprehensive knowledge about HIV has become one of the main strategies to reduce HIV transmission worldwide [ 9 - 12 ]. HIV knowledge of HIV was defined by United Nations General Assembly Special Session on HIV/AIDS (UNGASS) in 2001, an indicator defined by the identification of the two primary ways of preventing the sexual transmission of HIV and the rejection of the most common misconceptions about HIV transmission [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%